Drug induced pulmonary artery hypertension in a parturient-diagnostic challenge - Ramanathan, Ramayee; Natarajan, Usha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
A 28-year-old gravida 2 abortion 1 at 40 weeks of gestation, Rh Negative non iso-immunized with no other obstetric or medical comorbidities and uneventful antenatal period was admitted for induction of labor on date. In view of pathological cardiotocography with fetal distress, she was taken up for emergency caesarean section under epidural anaesthesia. After delivery of the baby, she had postpartum haemorrhage (PPH) which was controlled with uterotonics. But immediately after administration of intramuscular carboprost, she had ectopic beats on echocardiogram (ECG) monitor, for which she was evaluated postoperatively and diagnosed as pulmonary artery hypertension. As diagnosis of exclusion, drug induced pulmonary artery hypertension was made. This case report insists on importance of continuous vitals and cardiac monitoring while treating PPH to predict and prevent the major complications associated with medications used for management of PPH.